2019
DOI: 10.1111/jpc.14643
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of anti‐Mullerian hormone with humanchorionic gonadotropin test in the evaluation of testicular function of children with 46 XY male hypogonadism: Use of anti‐Mullerian hormone as abiomarker

Abstract: Aim It is challenging to evaluate reproductive potential during childhood. These challenges necessitate the use of invasive dynamic tests. Although the anti‐Mullerian hormone (AMH) is a reliable biomarker in evaluating testicular function, especially in the pre‐pubertal period, there are uncertainties concerning its use in a clinical setting. This study is focused on comparing the AMH and human chorionic gonadotropin (hCG) test in boys with hypogonadism. Methods A total of 160 boys aged between 0 and 18 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Our results showed a positive correlation between AMH level and post-HCG stimulation DHT and testosterone levels. However, there was no significant correlation between the In our study, 90 % patients with PAIS, 100% of patients with 5-alpha-reductase deficiency and 90 % of those with anatomical defects had normal AMH levels, which was consistent with the results of Szarras-Czapnik et al (36) Also Karaoglan reported normal AMH in patients with AIS and those with anatomical defects; however, the authors also found relatively low AMH levels in patients with 5-alpha-reductase deficiency (37). Our results demonstrated low AMH levels in more than half of patients with partial gonadal dysgenesis, which agreed with the results of Karaoglan (37).…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed a positive correlation between AMH level and post-HCG stimulation DHT and testosterone levels. However, there was no significant correlation between the In our study, 90 % patients with PAIS, 100% of patients with 5-alpha-reductase deficiency and 90 % of those with anatomical defects had normal AMH levels, which was consistent with the results of Szarras-Czapnik et al (36) Also Karaoglan reported normal AMH in patients with AIS and those with anatomical defects; however, the authors also found relatively low AMH levels in patients with 5-alpha-reductase deficiency (37). Our results demonstrated low AMH levels in more than half of patients with partial gonadal dysgenesis, which agreed with the results of Karaoglan (37).…”
Section: Discussionsupporting
confidence: 92%
“…Considering that the patient's genital development was in the G2PH2 stage, we deemed it necessary to monitor testicular function. Karaoglan et al's [ 10 ] study suggests that AMH testing could serve as a reliable and practical biomarker for evaluating testicular function in adolescents with hypogonadism. INH B is a good indicator of the degree of supporting cell differentiation, and its concentration is related to spermatogenic function [ 11 ].…”
Section: Discussionmentioning
confidence: 99%